Penegakan Hukum Pidana Terhadap Pelaku Penambangan Galian C Di Daerah Aliran Sungai Bingai - Arjuna, Arjuna; Arjuna; Syahrin, Alvi; Yunara, Edi; Marlina, Marlina (UNES Law Review, 2024)
Mining of minerals without a permit is a mining activity that has a big impact, especially on the environment and the State administrative system. This study explores aspects of unlawful acts in cases of unlicensed mining that can be detrimental to the State and have an impact on the environment, focusing on the Bingai River Watershed, Langkat Regency. This research aims to reduce, overcome, and analyze the interpretation of unlawful acts and implement material law against excavated mining actors in the Bingai River Basin. This research uses an empirical juridical approach with descriptive-analytical methods. Data was obtained from case studies at the Langkat District Environmental Service, Sei Bingai District SDA and Environment and other related legal materials, as well as in-depth legal literature regarding mining without permits and law enforcement. The results of this research show that criminal law enforcement against perpetrators of C-quarry mining in the Bingai river basin faces complex challenges, including interpreting unlawful acts, applying clear legal principles, and efforts to prevent unauthorized C-quarry mining activities in the Bingai river basin. . This research contributes to an understanding of the legal dynamics in enforcing criminal law against perpetrators of the criminal act of excavated mining in the Bingai river basin, as well as providing a basis for improving the law enforcement system and efforts to overcome the criminal act of excavated mining in the Bingai river basin.